Improvement of thermostability and catalytic efficiency of xylanase from Myceliophthora thermophilar by N-terminal and C-terminal truncation - Yang, Yue; Zhang, Chengnan; Lu, Hongyun; Wu, QiuHua; Wu, Yanfang; Li, Weiwei; Li, Xiuting (Frontiers in Microbiology, 2024)
Introduction Extracting xylanase from thermophilic filamentous fungi is a feasible way to obtain xylanase with good thermal stability. Methods The transcriptomic data of Myceliophthora thermophilic destructive ATCC42464 were differentially expressed and enriched. By comparing the sequences of Mtxylan2 and more than 10 xylanases, the N-terminal and C-terminal of Mtxylan2 were truncated, and three mutants 28N, 28C and 28NC were constructed. Results and discussion GH11 xylan Mtxylan2 was identified by transcriptomic analysis, the specific enzyme activity of Mtxylan2 was 104.67 U/mg, and the optimal temperature was 65°C. Molecular modification of Mtxylan2 showed that the catalytic activity of the mutants was enhanced. Among them, the catalytic activity of 28C was increased by 9.3 times, the optimal temperature was increased by 5°C, and the residual enzyme activity remained above 80% after 30 min at 50–65°C, indicating that redundant C-terminal truncation can improve the thermal stability and catalytic performance of GH11 xylanase.